Pengetahuan, kemahiran dan sikap guru-guru disiplin dalam melaksanakan tugas di sekolah menengah - Lim, Seo Peng (2010)
School teachers play the role and hold responsibility of an educator. However, teachers are facing a lot of pressure and obstacles while educating others. This research aims to study the level of knowledge, level of skill posses by a discipline teacher and the attitude they adopt during the course of their duty. A pilot project is conducted on 10 school teachers who are not respondent of this research and the alpha crombach is 0.76 for level of knowledge, 0.89 for level of skill and 0.79 for attitude. Subsequently, questionnaires are sent to 280 teachers from three secondary schools in the area of Permas Jaya, Johor Bahru. Respondents are required to complete the questionnaire in 4 sections. Section A collects the personal data of the respondent. Section B finds out the level of knowledge possess by the discipline teacher while section C looks into the level of skill and section D examines the attitude of the discipline teachers. The finding shows that the level of knowledge in the aspect of discipline is at the medium level. The level of skill possess by the teachers is also at the medium level. The result of the research shows no significant difference between male and female teachers in the level of knowledge and skill when they carry out their duties as discipline teachers. On the contrary, the t-test shows a significant difference between male and female teachers in term of attitude. Overall, there is room for improvement in the level of knowledge and skill for the discipline teachers. It is suggested that the relevant authorities such as Teacher Training Centre should plan and develop more suitable programmes to assist teachers in order to become a more efficient and effective discipline teacher in secondary school.